A modified three rail shear test procedure for rigid foamed materials. (May 2022) - Taskin, Melis; Sargin, Tugce; Aliyev, Raphiq; Cagdas, Izzet U
In this study, a modified three rail shear test (or double shear test) procedure is described for the determination of the shear moduli and the shear strength values of rigid foamed materials and test results are presented for light extruded polystyrene, which is a typical core material used in sandwich construction. The main idea is to obtain a nearly uniform shear stress distribution in the shear test specimens by strengthening them against bending. First, using a finite element model, it is numerically shown that a nearly pure shear stress state may be obtained in the strengthened three rail shear test specimens. Then, it is shown that the finite element numerical results obtained for the strengthened specimens are in excellent agreement with the analytical results. Next, three rail shear tests are performed on bare and strengthened specimens and the experimental results obtained are presented in comparison with the analytical results. Also, clamped beam vibration and three-point bending tests are conducted to validate the shear modulus values obtained. The results obtained show that, the strengthened three rail shear test specimens yield more accurate results for both shear modulus, and strength comparing with the bare specimens.